Full bloom : a novel - Serritella, Francesca Scottoline (Ballantine Books, 2025)
"The power to be seen. The power to be heard. The power to be adored. . . A woman's life is forever changed by a mysterious perfume in this stunning novel about ambition and untapped desire from the New York Times bestselling author of Ghosts of Harvard"-- Provided by publisher.